Sacrifice for a brand: Three expert visions of the fans relationships towards a football club - Cayolla, R. (2021)
This research was carried out with the aim of contributing to understanding of the concept of sacrifice associated with marketing and the relationship between brand and consumer. Fundamentally what we want to know is, in general, what leads someone to make sacrifices for a brand. We seek a “deep understanding of the actors, interactions, sentiments, and behaviors occurring for a specific process through time” (Woodside, 2010, p. 6). The areas of philosophy, journalism and football analysis were chosen because of the broad spectrum in society. There are two main objectives: 1st to search for a different perspective to understand the phenomenon; 2nd to have a global idea about football and fans. This is another step towards understanding the fans, the environment, the context and also the football phenomenon in a broader perspective.